Population-level factors associated with maternal mortality in the United States, 1997-2012 - Daniel B. Nelson; Michelle H. Moniz; Matthew M. Davis (BMC, 2018)
Abstract Background In contrast to peer nations, the United States is experiencing rapid increases in maternal mortality. Trends in individual and population-level demographic factors and health trends may play a role in this change. Methods We analyzed state-level maternal mortality for the years 1997-2012 using multilevel mixed-effects regression grouped by state, using publicly available data including whether a state had adopted the 2003 U.S. Standard Certificate of Death, designed to simplify identification of pregnant and recently pregnant decedents. We calculated the proportion of the increase in maternal mortality attributable to specific factors during the study period. Results Maternal mortality was associated with higher population prevalence of obesity and high school non-completion among women of childbearing age; these factors explained 31.0% and 5.3% of the attributable increase in maternal mortality during the study period, respectively. Among delivering mothers, prevalence of diabetes (17.0%), attending fewer than 10 prenatal visits (4.9%), and African American race (2.0%) were also associated with higher maternal mortality, as was time-varying state adoption of the 2003 death certificate (31.1%). Conclusions Our findings indicate that, in addition to better case ascertainment of maternal deaths, adverse changes in chronic diseases, insufficient healthcare access, and social determinants of health represent identifiable risks for maternal mortality that merit prompt attention in population-directed interventions and health policies.